Strategi Pengelolaan Kelas Sebagai Upaya Mengatasi Kejenuhan Belajar SKI Ma Al-Amien 1 Pragaan - Annisa Ummul Maghfiroh; Jauharotul Makniyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
A teacher's role is to help students improve the quality of their education. So teachers must be able to improve student achievement with the various abilities they have. In the learning process the problem faced by a teacher is classroom management. Classroom management is a teacher's skill to create and maintain optimal learning conditions so that they can restore them if disruptions occur in the teaching and learning process. Therefore, teachers must be able to manage the learning process in the classroom well by implementing learning strategies, especially in the subject of Islamic cultural history. The problem raised in this research is the teacher's strategy for overcoming SKI learning boredom at MA Al-Amien I Pragaan, which is described in two research focuses, namely: 1. What are the classroom management strategies as an effort to overcome SKI learning boredom at MA Al-Amien I Pragaan 2. What are the supporting and inhibiting factors that influence classroom management strategies as an effort to overcome SKI learning boredom at MA Al-Amien I Pragaan. This research was designed using a descriptive qualitative approach. The data collection techniques used were observation, interviews and documentation. From this method, researchers then process and analyze to obtain data or information. The subjects of this research were taken from teachers and students. Data analysis uses data reduction, data presentation and conclusions. For data validity, researchers used source triangulation. The results of this research are: 1. Class management strategies as an effort to overcome SKI learning boredom, namely: a. Using various methods, namely: discussion method, lecture method, mind mapping method, clipping method. b. Changes in class formation 2. Supporting and inhibiting factors that influence class management strategies in SKI learning, namely: a. teacher competency, b. students' abilities, c. classroom facilities and atmosphere.